Residents’ perceptions of the 2010 FIFA World Cup three months prior to the event: a case study of a suburb in Cape Town, South Africa - Bama, Hilary Kennedy Nji (Cape Peninsula University of Technology, 2011)
The importance of conducting resident perception studies into the phenomenon of mega sports events cannot be over-emphasised; as such studies provide a unique platform by means of which to gauge the perceptions and attitudes of host communities with regards to the impacts of mega-events. In the context of South Africa’s hosting of the 2010 FIFA World Cup, and regarding the perceived impacts of the event on host communities, a couple of studies have been undertaken within the Green Point suburb of Cape Town. As a continuum of such studies, the current study is undertaken with the objectives of ascertaining whether any adaptations have occurred three months before kick-off of the event, and to further provide a platform for post-event longitudinal studies. Furthermore, in cases where changes in perceptions were recorded, previous studies carried out within the same study area were reflected upon. The target population in the study involved residents living within a 2- kilometre radius of the Cape Town Stadium situated in Green Point. A total of 400 questionnaires were administered to residents using a spatially based stratified random sampling method. The focus of the study was to examine the perceptions and attitudes of Green Point residents towards the development of the Cape Town Stadium and potential impacts of the 2010 World Cup on their community. Key findings of the study revealed the profile of Green Point residents to be predominantly male, with an average age of 38.2 years.
Thesis (MTech (Tourism and Events Management ))--Cape Peninsula University of Technology, 2011
Keywords: World Cup (Soccer) (2010); Soccer -- Tournaments -- South Africa; Sports and tourism -- South Africa; Community development, Urban -- South Africa